Contextual Factors for Aging Well: Creating Socially Engaging Spaces Through the Use of Deliberative Dialogues. (25th July 2017) - Canham, Sarah L; Fang, Mei Lan; Battersby, Lupin; Woolrych, Ryan; Sixsmith, Judith; Ren, Tori Hui; Sixsmith, Andrew
Abstract: Purpose of the Study: Home and community engagement are key contextual factors for aging well, particularly for older adults in vulnerable social positions. A community-based participatory action research project conducted in Western Canada examined how to best use the shared amenity spaces in a low-income seniors' apartment complex in order to connect services and programs with tenants and to provide opportunities for service providers and local stakeholders to build upon and create new relationships toward collaboration and service delivery. Design and Methods: Pre-move deliberative dialogue workshops ( n = 4) were conducted with stakeholders (e.g., service providers, developers, and municipal government employees). Workshop participants ( n = 24) generated ideas and plans on how physical and social environments can contribute to the social engagement of senior tenants. Results: Shared dialogue led to community investment and asset sharing by integrating the knowledge and experiences of multiple stakeholder groups into the planning process. This article highlights how collaborative planning approaches for the effective use of the social environment (e.g., social programming), within the physical environment (e.g., amenity and community spaces), can generate rich and illuminating data for informing enhancements in the social environment of apartment dwelling low-income seniors. Contextual challenges to service provision are discussed, including the need for communication about and coordination of on-site programming, culturally diverse and responsive programming, and long-term funding. Implications: Prolonging independent community living with the assistance of support services should be a goal to both delay premature relocation into institutional care and meet the preferences of older adults.